TROMBOEMBOLISMO ARTERIAL FELINO: RELATO DE CASO - Miranda, Kaiane Lorenzi; Vaccarin, Charline Vanessa; Lusa, Fabrieli Tatiane; Lusa, Fabrieli Tatiane; Festugatto, Rafael; Pinheiro, Fernanda (Anais de Medicina Veterinária, 2022)
.